A step inside the aesthetics - Seel, Martin; Pereira Restrepo (Traductor), Sebastián (Estudios de Filosofía, 2007)
Since the days of Plato, aesthetic theory has been often obsessed by an alternative between being and semblance (Sein und Schein). According to this xation, aesthetic consciousness paves the way either to some higher reality or out of the reaches of reality as such. Either way, aesthetic perception is conceived of as fight from the phenomenal presence of human life. This article recommends that this disastrous consequence should not be accepted. For it is far more plausible to comprehend aesthetic consciousness ought as an excellent form of intuiting presence. This turn to the presence of something present —to its appearing (Erscheinen)—, it is argued, is a basic propelling force of all aesthetic perception.